Konsep dan Perhitungan Bagi Hasil pada Penghimpunan Dana (Funding) di Bank Syariah - Hartono, Rudi (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2019)
Sharia bank fund raising products are known as deposits, which generally consist of demand deposits for wadiah, mudharabah savings deposits, and deposits. The operational principle in Islamic banks that are applied in collecting public funds is the principle of wadi'ah and mudharabah. In the case of the authority of the mudharabah law is divided into two, namely mudharabah mutlaqoh and mudharabah muqoyyadah. The steps taken in calculating the profit-sharing of funds in Islamic banks include using the revenue sharing method, separating funds originating from mudharabah investment, calculating all total funds, calculating the average financing, summing total income, subtracting the percentage of investment, and determining the amount of profit obtained. The method used in deriving revenue sharing for depositors in Islamic banks is to use the calculation of investment returns per thousand and use profit-sharing calculations based on the average daily balance of all deposits and similar distribution income